1987
DOI: 10.1172/jci112839
|View full text |Cite
|
Sign up to set email alerts
|

Membrane skeletal alterations during in vivo mouse red cell aging. Increase in the band 4.1a:4.1b ratio.

Abstract: We have examined membrane protein profiles for alterations during red blood cell aging. To obtain populations of in vivoaged red cells, we maintained mice in a state ofcontinuous erythropoietic suppression for up to 8 wk using serial hypertransfusion. The circulating tl/2 of red cells from mice which had been erythropoietically suppressed for 8 wk was < 1 d compared with a t1/2 of 15 d for red cells from normal animals. The most obvious alteration in membrane proteins was an increase in the ratio of the membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
3

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 26 publications
4
43
0
3
Order By: Relevance
“…Thus, demonstrating a correlation between erythrocyte enzyme levels and density may confirm an enrichment of young cells at the top of a density gradient, but may not define the relative age of denser cells. Recently, studies of red cells from mouse and from man have suggested that the ratio of protein 4.la to 4.lb is an internal aplasia have exceptionally high ratios of 4.la to 4.lb indicate marker of cell age; as erythrocytes circulate, progressively more that this ratio reflects the aging process of mature red cells as protein 4. l a is present in the cells (23,24). The findings of well as the process of reticulocyte maturation.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, demonstrating a correlation between erythrocyte enzyme levels and density may confirm an enrichment of young cells at the top of a density gradient, but may not define the relative age of denser cells. Recently, studies of red cells from mouse and from man have suggested that the ratio of protein 4.la to 4.lb is an internal aplasia have exceptionally high ratios of 4.la to 4.lb indicate marker of cell age; as erythrocytes circulate, progressively more that this ratio reflects the aging process of mature red cells as protein 4. l a is present in the cells (23,24). The findings of well as the process of reticulocyte maturation.…”
Section: Discussionmentioning
confidence: 85%
“…33,34 In the original protocol 33,34 about 50 mice were used for serial transfusions to yield one animal enriched for sRBC. In our optimized protocol, we used only 10 mice for the same purpose.…”
Section: Discussionmentioning
confidence: 99%
“…32 In addition, the arrest of erythropoiesis by hypertransfusion was used to enrich blood with naturally aged RBC that could be characterized. 33,34 RBC from such treated rats and mice showed alterations in membrane components such as changes in the band 4.1a to 4.1b ratio and decreased cell volume, but they were not used to elucidate the mechanism of EPC.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery that the ratio of protein 4.1a to protein 4.1b, which are a part of the red cell membrane cytoskeleton, is correlated with erythrocyte life span in mammals [7][8][9], several authors have adopted the 4.1a/4.1b ratio as a parameter to characterize the absolute age of density-fractionated human erythrocytes [10][11][12]. Results obtained so far have shown that the population of circulating red cells is in fact very heterogeneous, with respect to membrane surface, cell volume, cation and water content, and cell deformability [12,13].…”
Section: Introductionmentioning
confidence: 99%